A REVIEW OF QUALITY CONTROL IN HISTOCHEMISTRY AND IMMUNOHISTOCHEMISTRY STAINING - Yustina Nuke Ardiyan (Berkala Ilmiah Kedokteran Duta Wacana, 2020)
Background: Tissue staining methods need controls to give best quality results. Controls is necessary to support the validity, correctness, and reliability of the staining results. Haematoxylin and Eosin (HE) and immunohistochemistry (IHC) staining require different control quality. Objective: To discuss the utilization of controls used in tissue staining. Method: This is a narrative review with literature from 2008-2016. Results: Routine staining usually does not require any control. Specific stainings require controls to support the validity, correctness, and reliability of the staining results. Histochemistry staining requires only positive control, while positive and negative controls must be included in IHC staining. A tissue section which expresses the protein of interest is reffered to positive control, whereas those without any target antigen expression are defined as negative control. Conclusion: Histochemistry and IHC staining controls are needed to obtain the validity of the tissue or cell samples.